Avaliação do controle da pressão arterial de indivíduos acompanhados por um serviço de atenção psicossocial - Cavalcante, Jaciane Araújo (Universidade Federal do Tocantins, 2018)
Introduction: Mental disorders are characterized by being clinically significant disturbances in the cognition, emotional regulation or behavior of the individual and reflect a dysfunction in the psychological, biological or developmental processes underlying mental functioning. Individuals with this diagnosis may be affected by other chronic conditions associated with drug treatment, including arterial hypertension, requiring constant monitoring. Objectives: Evaluate the monitoring of blood pressure and body mass index of people with mental disorders accompanied by Palmas psychosocial care services type II, from 2010 to June 2016. Methodology: Descriptive cross-sectional, analytical, retrospective, with data collection in medical records in association with the field study, with a qualitative approach from the grounded theory perspective. Data collection performed between April and September 2017, through a structured form elaborated by the researcher and field diary. Included in the study were the records of persons admitted to the unit aged 18 years and 60 years, who were attended in the period between January 2010 and June 2016, with a total of 246 participants. Microsoft Excel 2010 and Epi Info 3.4.3 applications were used for data processing and analysis. Results: One hundred twenty-three participants were female and one hundred twenty-three males, aged between 29 and 50 years (69%). The proportion of users with schizophrenia and other psychotic disorders were 56.95% and that of bipolar disorders and other psychotic disorders was 21.3%. Among the medications prescribed, there was a predominance of antipsychotics and neuroleptics (33.1%), followed by mood stabilizers (18.51%), being in consonance with the medical diagnoses. Most cases do not have continuous monitoring of blood pressure, weight, height and BMI, and of the sample selected, only 28.05% had all the necessary data in the medical record. Regarding the use of alcohol, tobacco and other drugs, 17.88% reported using one or more drugs, 23.57% refused to use any substance, and 58.53% didn’t have information in medical records. Conclusion: The results indicate that monitoring of blood pressure, verification of body mass index, as well as the existence of other factors that influence treatment among users of a mental health service, helps to rethink the preventive and educational actions in this public . Secondary health care in the city requires the quality of access to the user, working as a coordinator of the psychosocial care network. The CAPS II as a specialized service in psychiatric disorders should pay attention to the needs of the users as a whole, and with a focus on the discussion of cases in primary care, allows the articulation between primary and specialized care working full care.